Astrovirus Encephalitis in Boy with X-linked Agammaglobulinemia - Quan, Phenix-Lan (Centers for Disease Control and Prevention, 2010)
Encephalitis is a major cause of death worldwide. Although >100 pathogens have been identified as causative agents, the pathogen is not determined for up to 75% of cases. This diagnostic failure impedes effective treatment and underscores the need for better tools and new approaches for detecting novel pathogens or determining new manifestations of known pathogens. Although astroviruses are commonly associated with gastroenteritis, they have not been associated with central nervous system disease. Using unbiased pyrosequencing, we detected an astrovirus as the causative agent for encephalitis in a 15-year-old boy with agammaglobulinemia; several laboratories had failed to identify the agent. Our findings expand the spectrum of causative agents associated with encephalitis and highlight unbiased molecular technology as a valuable tool for differential diagnosis of unexplained disease.